2010
DOI: 10.1128/iai.01192-09
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosaAlginate PromotesBurkholderia cenocepaciaPersistence in Cystic Fibrosis Transmembrane Conductance Regulator Knockout Mice

Abstract: Pseudomonas aeruginosa, a major respiratory pathogen in cystic fibrosis (CF) patients, facilitates infection by other opportunistic pathogens. Burkholderia cenocepacia, which normally infects adolescent patients, encounters alginate elaborated by mucoid P. aeruginosa. To determine whether P. aeruginosa alginate facilitates B. cenocepacia infection in mice, cystic fibrosis transmembrane conductance regulator knockout mice were infected with B. cenocepacia strain BC7 suspended in either phosphate-buffered saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 44 publications
3
33
0
Order By: Relevance
“…However, it is likely that CFTR dysfunction predisposes the host to infection with P. aeruginosa ; subsequent adaptation by the bacteria then allows for chronic infection and reduced opportunity for eradication. It is also likely that P. aeruginosa interacts with other bacterial pathogens including Staphylococcus aureus and Burkholderia cepacia complex in a way to further alter the inflammatory response 25,82 .…”
Section: Host- Response In Cf Lung Diseasementioning
confidence: 99%
“…However, it is likely that CFTR dysfunction predisposes the host to infection with P. aeruginosa ; subsequent adaptation by the bacteria then allows for chronic infection and reduced opportunity for eradication. It is also likely that P. aeruginosa interacts with other bacterial pathogens including Staphylococcus aureus and Burkholderia cepacia complex in a way to further alter the inflammatory response 25,82 .…”
Section: Host- Response In Cf Lung Diseasementioning
confidence: 99%
“…Nonetheless, the precise ways under which the many different organisms interact within the CF airways, and how these interactions influence the behavior of the individual species, the activity of the polymicrobial communities, and the relationship between host and microbes are poorly understood. Some studies have highlighted the potentially important roles of such interspecies interactions in disease phenotype and clinical outcome of CF infections (Amin et al, 2010; Chattoraj et al, 2010; Bragonzi et al, 2012; Lopes et al, 2012; Twomey et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, and as previously underlined, infections of the CF airways is highly polymicrobic and there is growing evidence that many of these microorganisms interact (Sibley & Surette, 2011) as observed between P. aeruginosa and S. aureus (Biswas et al, 2009;Hoffman et al, 2006;Mitchell et al, 2010b;Qazi et al, 2006;Yang et al, 2011), P. aeruginosa and Burkholderia spp. (Bakkal et al, 2010;Chattoraj et al, 2010;Riedel et al, 2001;Weaver & Kolter, 2004), P. aeruginosa and S. maltophilia , P. aeruginosa and C. albicans (McAlester et al, 2008), and more generally with a large proportion of the organisms found in the CF airways (Duan et al, 2003;Sibley et al, 2008).…”
Section: Interspecies Interactions Between Cf Pathogensmentioning
confidence: 99%